Economic determinants of regional trade agreements - Alhassan, Osman (Kansas State University, 2016)
The literature concerning the economics of regional trade agreements (RTAs) has evolved from a theoretical perspective to an empirically based approach over the past decade. Specifically, this report examines the various empirical studies on the economic determinants of RTAs and the likelihood of RTAs between country-pairs. Scott L. Baier and Jeffrey H. Bergstrand (2004) or BB (2004) provide us the first empirical work on the economic determinants of RTAs. Their model predicts fairly accurately, 85% of the 286 RTAs in 1996 among 1431 country-pairs, and 97% of the remaining 1145 pairs with no RTAs based on economic features. In this report, we begin with an introduction to RTAs, and then we will explore the contribution of BB (2004), as well as other economists’ empirical findings on the economics of RTAs, using empirical strategies similar to BB’s (2004) study.
Keywords: Regional trade agreements